2023
DOI: 10.3390/biology12101324
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Ultrafast Doppler Imaging Combined with Confocal Microscopy and Behavioral Approaches to Gain Insight into the Central Expression of Peripheral Neuropathy in Trembler-J Mice

Mariana Martínez Barreiro,
Lucia Vázquez Alberdi,
Lucila De León
et al.

Abstract: The main human hereditary peripheral neuropathy (Charcot-Marie-Tooth, CMT), manifests in progressive sensory and motor deficits. Mutations in the compact myelin protein gene pmp22 cause more than 50% of all CMTs. CMT1E is a subtype of CMT1 myelinopathy carrying micro-mutations in pmp22. The Trembler-J mice have a spontaneous mutation in pmp22 identical to that present in CMT1E human patients. PMP22 is mainly (but not exclusively) expressed in Schwann cells. Some studies have found the presence of pmp22 togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(115 reference statements)
0
0
0
Order By: Relevance
“…Our results show that TrJ mice present an altered central nervous response in comparison with WT, indicating a compromise of the neurovascular system due to the disease. The present work complements our previous observations around the hippocampal domains, where we showed there is a deterioration of the vascular hemodynamic component in normal murine ageing 40 and an increase in blood flow associated with anxiousness in TrJ mice in comparison to WT mice 41 .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results show that TrJ mice present an altered central nervous response in comparison with WT, indicating a compromise of the neurovascular system due to the disease. The present work complements our previous observations around the hippocampal domains, where we showed there is a deterioration of the vascular hemodynamic component in normal murine ageing 40 and an increase in blood flow associated with anxiousness in TrJ mice in comparison to WT mice 41 .…”
Section: Introductionsupporting
confidence: 90%
“…This may be due to a failure of the global connectivity maintenance mechanisms as a result of an altered vascular physiology, with perhaps a preponderance of spontaneous global vasomotion (Mayer waves) over local neurovascular coupling. We have recently demonstrated that in RS, the CBV of TrJ mice, showed a significantly increased value with respect to WT mice, associated with significant vessel volume values increase, detectable as early as three months old mice 41 .…”
Section: Discussionmentioning
confidence: 89%